Judicial Efficiency and Firm Productivity: Evidence from a World Database of Judicial Reforms - Chemin, Matthieu (The Review of Economics and Statistics, 2020)
I assemble and classify a database of judicial reforms funded by foreign aid agencies as either comprehensive (targeting all characteristics of quality, speed, access) or limited reform. A triple difference is used to compare firms in countries with or without judicial reforms, before and after reforms, and in sectors more or less reliant on contract enforcement mechanisms, due to their need for relationship-specific investments. I find that externally financed comprehensive judicial reforms improve perceptions of judiciary efficiency (for all firms) and firm productivity (for sectors relying on relationship-specific investments) by 0.15 and 0.09 (22%) standard deviation, respectively.